Self-assembled stretchable photonic crystal for a tunable color filter - Cho, Hyunmin; Han, Seungyong; Kwon, Jinhyeong; Jung, Jinwook; Kim, Hyun Jong; Kim, Hyunseok; Eom, Hyeonjin; Hong, Sukjoon; Ko, Seung Hwan (Optics Letters, 2018)
In this Letter, we report the development of a continuously tunable color filter based on a self-assembled isotropically stretchable microbead monolayer. Spreading equidistantly upon the application of lateral strain, the isotropically stretchable monolayer serves as a dynamic diffraction grating whose diffraction angle can be mechanically modulated. Combined with a simple spatial filtering scheme, the spectra of the filtered light are solely controlled by external strain (up to 32% radial strain) to cover a broad visible spectrum. Through a finite-difference time-domain far-field diffraction simulation, we validate the working principle of the proposed color filter. The proposed continuously tunable color filter is expected to open original applications in next-generation display field.
Keywords: Diffraction angle; Dynamic diffraction; External strains; Far field diffractions; Lateral strain; Spatial filterings; Stretchable photonics; Visible spectra